(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article focuses on the unique role of nomination in the formation of terminological systems in studies in the field of Uzbek linguistics. When investigating terms related to computer and internet topics, it is necessary to establish the theoretical foundations of the terms. Therefore, the analysis of their nominative characteristics examined well-known views on terminology, term systems, primary and secondary nominative phenomena.